KETERAMPILAN MENYIMAK SISWA KELAS III SEKOLAH DASAR : STUDI KASUS BERBASIS PERSPEKTIF GURU DI SDN 13/I MUARA BULIAN - Audy Mita Amelina; Anggia Tri Agustina; Cindy; Khoirunnisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Listening skills constitute the primary foundation of language acquisition, yet they often receive insufficient attention in lower-grade instruction. This study aims to describe the listening skill level of Grade III A students at SDN 13/I Muara Bulian, identify the factors influencing these skills, and analyze the teaching strategies and evaluation instruments employed by the teacher. A qualitative approach with a single case study design was adopted. Data were collected through semi-structured interviews with the homeroom teacher and corroborated through source triangulation with students. Data analysis followed Miles and Huberman’s interactive model. Findings indicate that 92.9% of students (26 out of 28) achieved listening learning targets, substantially exceeding the averages reported in comparable studies. The dominant factors affecting listening skills were student concentration (focus span approximately 20 minutes) and peer disturbance. Six primary strategies were implemented: Reading Aloud, creative lesson openers with oral quizzes, structured focus-time management, active personal approaches, strategic seating for hyperactive students, and a reward system. Assessment was conducted through oral and written questions covering recall and comprehension levels. This study concludes that the teacher’s role as an active and responsive facilitator is the primary determinant of listening instruction success in lower grades. These findings imply the need for developing lower-grade teachers’ pedagogical competence in designing systematic, student-need-oriented listening instruction.